SHM_415449_HST_3D Thick-Butted Stone Axe with a Flared Edge - Lernestål, Erik; Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a thick-butted stone axe with a flared edge from the Swedish Late Neolithic collected from Skåne in 1854 and currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=514

Link to Sök I Samlingarna

https://samlingar.shm.se/object/041158E9-A1C1-412A-9611-94D7F7D7B9AD
Keywords: Museum Object; 3D Model; Archaeology; Archaeology; Photogrammetry; Archaeology/history; History and archaeology; Dynamic Collections; Swedish Late Neolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi